Nilai Moral: Cerita Kain dan Habel dalam Alkitab Perjanjian Lama - Pilenia; Mika Melliani; Citra Sistawati; Helnita; Sarmauli (LPPM STT Baptis Kalvari, 2023)
This research uses qualitative methods with a focus on retelling the story of Cain killing Abel. Qualitative methods are used to deepen understanding of the symbolic role of Cain and Abel in the biblical text, especially in the Book of Genesis. The data collection technique used in this research is through analysis of various scientific journals that are relevant to the topic studied. Researchers identify and collect information related to the story of Cain and Abel from trusted and quality scientific sources. The main approach applied in this research is a semiotic approach. Through this approach, the author carries out an in-depth analysis of the symbolism contained in the story of Cain and Abel. The semiotic approach allows researchers to explore theological meanings and concepts that may be hidden behind the biblical narrative. During the research process, the author critically analyzed the symbolic meanings found in the biblical text, and the main goal was to support a richer understanding of the theological concepts contained in the story. The results of this research provide deep insight into the symbolic relationship between Cain and Abel, and contribute to theological understanding within a Biblical framework. This analysis also highlights the relevance of symbolic meaning in the context of theology and spiritual life, making an important contribution to theological literature and biblical understanding.